2017
DOI: 10.18697/ajfand.80.17315
|View full text |Cite
|
Sign up to set email alerts
|

Modalites de consommation et valeur nutritionnelle des legumineuses alimentaires au Burkina Faso

Abstract: RESUMEAu Burkina Faso les légumineuses constituent une source importante de nutriments pour les populations. La présente étude a eu pour objectif de déterminer la valeur nutritionnelle et la place des légumineuses dans le régime alimentaire des ménages à Ouagadougou, Kaya, Lebda et Nobéré. La méthodologie a consisté en une enquête de consommation alimentaire auprès de 325 ménages et à déterminer les teneurs en macronutriments et en minéraux fer, zinc et calcium de six (6) variétés de légumineuses. Il en résult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 18 publications
0
3
0
2
Order By: Relevance
“…Accordingly, the non-proteinogenic amino acids reported from Senegalia seeds are discussed in section 5.6. Besides, Guissou et al (2017) have reported a large discrepancy between the sum of 17 proteinogenic amino acids' content (7.8 g/100 g dm) and crude protein content (35-40 g/100 g dm) (Drabo et al, 2020;Hama-Bâ et al, 2017;Msika et al, 2017) from S. macrostachya seeds, suggesting a high content of non-protein nitrogen. The amount of data is very limited and inconsistent, making it difficult to conclude the nutritional property of Senegalia seed proteins.…”
Section: Protein Nutritional Quality and Functional Propertiesmentioning
confidence: 98%
“…Accordingly, the non-proteinogenic amino acids reported from Senegalia seeds are discussed in section 5.6. Besides, Guissou et al (2017) have reported a large discrepancy between the sum of 17 proteinogenic amino acids' content (7.8 g/100 g dm) and crude protein content (35-40 g/100 g dm) (Drabo et al, 2020;Hama-Bâ et al, 2017;Msika et al, 2017) from S. macrostachya seeds, suggesting a high content of non-protein nitrogen. The amount of data is very limited and inconsistent, making it difficult to conclude the nutritional property of Senegalia seed proteins.…”
Section: Protein Nutritional Quality and Functional Propertiesmentioning
confidence: 98%
“…32,33 The cooked seed, known as "zamné" in the local language, is a health-promoting traditional food well appreciated in Burkina Faso. 34,35 The fermented seeds are also used as condiments. 36 SMS extracts have been incorporated in cosmetic products to prevent and treat disorders affecting the skin, mucosae, or appendages.…”
Section: Introductionmentioning
confidence: 99%
“…Elles contiennent entre 20 et 25 % de protéines soit deux et trois fois plus que le blé et le riz respectivement (FAO, 2016). En plus des protéines, les légumineuses ont une forte teneur en fibres, en minéraux (fer, magnésium, potassium, phosphore, zinc), en vitamines et une faible teneur en matières grasses et en sodium (Hama-Ba et al, 2017 ;Soumaré et al, 2020). La consommation des légumineuses contribue à réduire les risques à certaines maladies dont l'anémie, le cancer, le diabète et les maladies cardiaques car elles sont digestes et font baisser le taux de cholestérol (Rémond et Walrand, 2017).…”
Section: Symbioses Fixatrices D'azote : Types Et Interetsunclassified